Searching for information on the web: Impact of cognitive aging, prior domain knowledge and complexity of the search problems. Issue 1 (January 2017) - Sanchiz, M.; Chin, J.; Chevalier, A.; Fu, W.T.; Amadieu, F.; He, J.
Highlights: Prior domain knowledge improves older adults' query and navigation strategies and copes with the age-related decline of cognitive flexibility. Unlike prior results, older adults were outperformed by young ones in open-ended information problems. In open-ended information problems, older adults did not benefit from their prior knowledge and produced semantically less relevant queries as compared to fact-finding problems. Abstract: This study focuses on the impact of age, prior domain knowledge and cognitive abilities on performance, query production and navigation strategies during information searching. Twenty older adults and nineteen young adults had to answer 12 information search problems of varying nature within two domain knowledge: health and manga. In each domain, participants had to perform two simple fact-finding problems (keywords provided and answer directly accessible on the search engine results page), two difficult fact-finding problems (keywords had to be inferred) and two open-ended information search problems (multiple answers possible and navigation necessary). Results showed that prior domain knowledge helped older adults improve navigation (i.e. reduced the number of webpages visited and thus decreased the feeling of disorientation), query production and reformulation (i.e. they formulated semantically more specific queries, and they inferred a greater number of new keywords).